Current Status of Knowledge on Prevention of Complications of Outpatients with Hypertension at Vinmec Times City International General Hospital in 2025 - Phuc Phong, Nguyen; Thi Nguyet, Nguyen; Thi Thiem, Cao; Van Thao, Vu; Ngoc Sao, Nguyen; Thanh Nam, Nguyen; Thi Thuy, Ha; Thi My, Tran; Anh Son, Dang; Hai Ha, Tran; Van Chuyen, Mai; Thi Sinh, Hoang; et al. (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Abstract: Objective: To describe the current status of knowledge and analyze some factors related to knowledge of complication prevention among hypertensive outpatients. Methods: A cross-sectional descriptive study was conducted on 377 patients diagnosed with and managed for hypertension from January to June 2025. Results: Univariate analysis showed that males were 2.1 times more likely to have adequate knowledge compared to females; patients with college/university education or higher had better knowledge than those with high school education or lower (OR = 2.2). Non-smokers were 1.6 times more likely to have adequate knowledge compared to current or former smokers; those with a history of alcohol consumption were 2.0 times more likely; and individuals who were aware of hypertension complications had 1.8 times higher knowledge scores than those who were not aware (p < 0.05). In the multivariate regression model, three factors remained statistically significant: gender, educational level, and the presence of diabetes mellitus (p < 0.05). Conclusion: the study showed that the proportion of hypertensive patients with adequate knowledge of complication prevention was relatively high (74.5%). The main associated factors included male gender, higher educational level, non-smoking status, awareness of complications, and a history of diabetes mellitus. Keywords: Complications, prevention, knowledge, hypertension.